Sosialisasi Sistem Pengarsipan Guna Meningkatkan Tata Kelola Administrasi di Kampung Yanggandur Merauke - Umiyati Haris; Fransin Kontu; Hubertus Oja (UNIB Press, 2023)
The document archiving system in the government hierarchy of a village is crucial in today's modern era. Archiving aims to organise documents in the village organisation system as a form of village identity. This service aims to increase community understanding of the importance of archive management in the village administration system. This service was carried out in Yanggandur Village, Sota District, Merauke Regency. The method used in this service is delivering material on the Village Administration Filing System delivered through lecture and presentation methods. The result of the socialisation in this service is a real positive impact on efficiency, transparency, and village community services in the archiving process in the village administration system. Document management is also better organised through this socialisation which then results in three things. Firstly, there is an increase in efficiency in document management. Second, Better Information Accessibility, where this archiving system has brought significant changes in terms of information accessibility. Third, there is a reduced risk of data loss.